A review of the efficacy of intraarticular hip injection for patients with hip osteoarthritis: to inject or not to inject in hip osteoarthritis? - Rampal, Sanjiv; Jaiman, Ashish; Tokgöz, Mehmet Ali; Arumugam, Gayathri; Sivananthan, Sureshan; Jagdeb Singh, Rashdeep Singh; Zazali, Syafiqah; Mohaddes, Maziar (Turkish Joint Diseases Foundation, 2022)
Hip injection (HI) for osteoarthritis (OA) are in vogue nowadays. Corticosteroids (CSs) and hyaluronic acid (HA) gel are the two most common agents injected into the hip. Off late, platelet-rich plasma (PRP), mesenchymal stem cell (MSC), bone marrow aspirate concentrate (BMAC), local anesthetic (LA) agents, non-steroidal anti-inflammatory drugs (NSAIDs) and their different combinations have also been injected in hips to provide desired pain relief. However, there is a group of clinicians who vary of these injections. A search of the literature was performed on PubMed, Cochrane Library, and DOAJ using the keywords “hip osteoarthritis injection”. Data were analyzed and compiled. Intraarticular CSs are effective in providing the desired pain relief in OA hip, but repeated injections should be avoided and the interval between HI and hip arthroplasty must be kept for more than three months. Methylprednisolone or triamcinolone are combined with 1% lidocaine or 0.5% bupivacaine. Chondrotoxic effects of LA is a concern. Although national guidelines do not favor the use of HA for hip OA, numerous publications have favored its usage for a moderate grade of OA. The PRP, MSC, and BMAC are treatment options with great potential; however, currently, the evidence is conflicting on their role in hip OA. There is always a risk of septic arthritis, particularly when aseptic precautions are not followed, and clinicians must vary of this complication.